Assessment on the performance of bifacial monocrystalline solar photovoltaic panels in residential areas in Pampanga, Philippines - Edgardo M. Santos (International Journal of Advances in Applied Sciences, 2026)
This research compared bifacial photovoltaic (BPV) in Pampanga households in limiter-only, hybrid battery, and net-metering. To evaluate the energy output, performance ratio (PR), and grid dependency, seven setups (5.65-12.5 kWp) were monitored over 31-37 days with the help of data loggers. The net-metered system of 12.5 kWp became fully independent of the grid and produced 206% of the household demands. The most ideal PR (75.17%) was achieved at the 7 kWp net-metered system. Battery-based hybrid systems minimized grid reliance by 56% and systems based on limiters obtained half supply. Net-metered configurations considerably beat the other configurations (p <0.001). Results prove that BPV is viable in tropical homes, which endorses sustainable development goals (SDGs) 7 and SDG 13.